Exploiting β‐Amino Acid Enolates in Direct Catalytic Diastereo‐ and Enantioselective C−C Bond‐Forming Reactions. Issue 59 (8th October 2018) - Yu, Jin‐Sheng; Noda, Hidetoshi; Shibasaki, Masakatsu
Abstract: In contrast to the widespread use of α‐amino acid‐equivalent enolates for the preparation of non‐natural amino acids, the utilization of β‐amino‐acid counterparts has been limited. This deficit has resulted in a short supply of β 2,  2 ‐amino acids bearing two substituents at the α‐carbon, especially for peptide synthesis. Herein, racemic 4‐substituted isoxazolidin‐5‐ones were used as precursors of β 2 ‐amino acid enolates in the direct catalytic diastereo‐ and enantioselective C−C bond‐forming reactions, constructing two adjacent stereocenters in a highly stereoselective fashion. The obtained adducts were smoothly coupled with α‐amino acid‐derived α‐ketoacids to afford α/β 2,  2 ‐hybrid dipeptides suitable for 9‐fluorenylmethoxycarbonyl (Fmoc)‐based solid‐phase peptide synthesis. Moreover, the Mannich adducts obtained from isatin‐derived imines were converted to spirocyclic β‐lactams, which have recently received increased attention due to their unique biological activities and conformational preferences. Abstract : Direct bonding : Direct catalytic diastereo‐ and enantioselective C−C bond‐forming reactions by using β‐amino acid enolates are presented. The obtained products are easily converted to α/β‐hybrid dipeptides suitable for 9‐fluorenylmethoxycarbonyl‐based solid‐phase peptide synthesis. Furthermore, the synthesis of a spirocyclic β‐lactam embedded in a peptide backbone is demonstrated.